ANALISIS KEPUASAN PENGUNJUNG DAN POTENSI PENGEMBANGAN PADA OBJEK WISATA PANTAI MUTUN DI KABUPATEN PESAWARAN - Vela Trecylia; Firdasari .; Lina Marlina (Lampung University, 2023)
This study aims to analyze the level of visitors’ satisfaction at Mutun Beach, the tourist attributes that need to be improved and maintained by Mutun Beach, and to find out the driving and inhibiting factors development of Mutun Beach. The method used in this research was a survey method. The samples in this study were 4 Mutun employees and 77 visitors, which were taken using purposive sampling and accidental sampling methods. Data collection was carried out in January - February 2023. The data analysis methods used were Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and descriptive analysis. The results of this study indicated that the level of visitor satisfaction is in the